Research progress on the role of hormones in ischemic stroke - Huang, Shuyuan; Liu, Lu; Tang, Xiaodong; Xie, Shulan; Li, Xinrui; Kang, Xianhui; Zhu, Shengmei (Frontiers in Immunology, 2022)
Ischemic stroke is a major cause of death and disability around the world. However, ischemic stroke treatment is currently limited, with a narrow therapeutic window and unsatisfactory post-treatment outcomes. Therefore, it is critical to investigate the pathophysiological mechanisms following ischemic stroke brain injury. Changes in the immunometabolism and endocrine system after ischemic stroke are important in understanding the pathophysiological mechanisms of cerebral ischemic injury. Hormones are biologically active substances produced by endocrine glands or endocrine cells that play an important role in the organism’s growth, development, metabolism, reproduction, and aging. Hormone research in ischemic stroke has made very promising progress. Hormone levels fluctuate during an ischemic stroke. Hormones regulate neuronal plasticity, promote neurotrophic factor formation, reduce cell death, apoptosis, inflammation, excitotoxicity, oxidative and nitrative stress, and brain edema in ischemic stroke. In recent years, many studies have been done on the role of thyroid hormone, growth hormone, testosterone, prolactin, oxytocin, glucocorticoid, parathyroid hormone, and dopamine in ischemic stroke, but comprehensive reviews are scarce. This review focuses on the role of hormones in the pathophysiology of ischemic stroke and discusses the mechanisms involved, intending to provide a reference value for ischemic stroke treatment and prevention.